Functional and structural deficits at accumbens synapses in a mouse model of Fragile X - Neuhofer, Daniela; Henstridge, Christopher M.; Dudok, Barna; Sepers, Marja; Lassalle, Olivier; Katona, István; Manzoni, Olivier J. (Frontiers in Cellular Neuroscience, 2015)
Fragile X is the most common cause of inherited intellectual disability and a leading cause of autism. The disease is caused by mutation of a single X-linked gene called fmr1 that codes for the Fragile X mental retardation protein (FMRP), a 71 kDa protein, which acts mainly as a translation inhibitor. Fragile X patients suffer from cognitive and emotional deficits that coincide with abnormalities in dendritic spines. Changes in spine morphology are often associated with altered excitatory transmission and long-term plasticity, the most prominent deficit in fmr1-/y mice. The nucleus accumbens, a central part of the mesocortico-limbic reward pathway, is now considered as a core structure in the control of social behaviors. Although the socio-affective impairments observed in Fragile X suggest dysfunctions in the accumbens, the impact of the lack of FMRP on accumbal synapses has scarcely been studied. Here we report for the first time a new spike timing-dependent plasticity paradigm that reliably triggers NMDAR-dependent long-term potentiation (LTP) of excitatory afferent inputs of medium spiny neurons (MSN) in the nucleus accumbens core region. Notably, we discovered that this LTP was completely absent in fmr1-/y mice. In the fmr1-/y accumbens intrinsic membrane properties of MSNs and basal excitatory neurotransmission remained intact in the fmr1-/y accumbens but the deficit in LTP was accompanied by an increase in evoked AMPA/NMDA ratio and a concomitant reduction of spontaneous NMDAR-mediated currents. In agreement with these physiological findings, we found significantly more filopodial spines in fmr1-/y mice by using an ultrastructural electron microscopic analysis of accumbens core medium spiny neuron spines. Surprisingly, spine elongation was specifically due to the longer longitudinal axis and larger area of spine necks, whereas spine head morphology and postsynaptic density size on spine heads remained unaffected in the fmr1-/y accumbens. These findings togeth